Assessment of C-Shaped Canal Morphology in Mandibular and Maxillary Second Molars in an Iraqi Subpopulation Using Cone-Beam Computed Tomography. (16th March 2022) - Abdalrahman, Kazhan; Talabani, Ranjdar; Kazzaz, Sara; Babarasul, Dlsoz
Abstract : Endodontic treatment is basically dependent on knowledge of the root canal anatomy. The goal of this study was to use cone-beam computed tomography (CBCT) imaging to examine the C-shaped canal configuration of mandibular and maxillary second molars in an Iraqi subpopulation. The prevalence and configurations of C-shaped canals were evaluated in 368 mandibular second molars and 369 maxillary second molars using CBCT scans. The effects of gender, age, and unilateral/bilateral on the presence of C-shaped canals were investigated. Chi-square and Fisher's exact tests were used to determine the level of significance (p ≤ 0.05 ), and kappa value was used to check reliability of results of the research. In mandibular second molars, the prevalence of C-shaped canals was 17.4%. The prevalence was significantly higher in females (23%) than males (10.4%) using the chi-square test. There is no significant difference in the prevalence of C-shaped canal depending on age and tooth position. The C2 type was the most common (56.3%). This prevalence did not differ with gender, age, or tooth position. In maxillary second molars, C-shaped canals were present in 7.9%. Type I (subtype C) (fusion of 2 root canals MB-DB) was the most common type of fused root (65.5%). There is no significant difference in the prevalence of C-shaped canal depending on the type of fused root, age, and tooth position. The majority of C-shaped canals in mandibular second molars were bilateral in both genders, but unilateral presence was more common in maxillary second molars in both genders. Within the limits of this study, C-shaped canals were found to be more common in mandibular second molars than in maxillary second molars in an Iraqi subpopulation.